Decoration of CoFe-LDH/porous MgO composite with ZrO2 nanoparticles for efficient photocatalytic removal of indigo carmine - Tehseen Zehra; Ananda Repycha Safira; Arash Fattah-alhosseini; Mohammad Alkaseem; Mosab Kaseem (Journal of Magnesium and Alloys)
This study presents a novel photocatalytic system exploiting the unique properties of ZrO₂ and its integration with layered double hydroxide (LDH) films on porous coatings produced via plasma electrolytic oxidation (PEO). Herein, CoFe-LDH films were created on the porous surface of PEO-coated AZ31 Mg alloy using a hydrothermal treatment in cobalt and iron nitrate solutions, followed by a secondary hydrothermal process in a ZrO₂ solution for 10 h at 70 °C. The impact of ZrO₂ on the morphological, compositional, and photocatalytic performance was then compared to the case where ZrO₂ nanoparticles were electrophoretically incorporated into the porous PEO coating. Characterization results revealed that the ZrO₂-modified LDH coatings exhibited a dispersed flake-like structure with an increased surface area, a reduced band gap energy of 3.14 eV, and enhanced electron-hole separation. Experimental results demonstrated an outstanding 99.8% degradation of indigo carmine within 15 mins, with remarkable multi-cycle stability over five consecutive cycles without significant performance decline. This system demonstrates faster degradation rates and greater durability compared to previously reported catalysts, underscoring its potential for effective and sustainable environmental remediation. The synergistic integration of ZrO₂, LDH, and PEO highlights a promising strategy for wastewater treatment, particularly for the removal of persistent organic dyes like indigo carmine.